Developing proposal for the practice of recognizing and award-giving quality green space in Malaysia - Mohd Razali, Iskandar Al Khalifah (2022)
In Malaysia, the agenda to provide quality green space for its living environment was outlined within the National Landscape Policy. However, the aspiration towards it remained dormant and progressing slowly. Problems like the conflict and lacking of method to evaluate the quality green space worth and blunt adoption of approaches from temperate countries into tropical country can cause the Malaysia to experience shortage in quality green space. A popular and feasible approach is needed to garner everyone attention in bolstering the quality green space development in Malaysia. Hence, this study aims to identify a new approach for appraising, rate and assess quality green space in Malaysia. To gather this information, a personal interview using a semi-structured open-ended interview was conducted with 15 professionals involved in the Malaysian landscape industry. The interviews garnered their opinions, standpoint, and perceptions on the research subject concerning the state of recognition and awards in Malaysian landscape industry, factor affecting quality green space in Malaysia, and proposal for the recognition and awards scheme quality green space in Malaysia. Then, a thematic analysis was used to extrapolate the findings. The results elicit several important findings on the topic. First, there was no recognition and awards scheme for quality green space in Malaysia. Results also averred the recognition and award scheme was important to provide individual, group or product a formal recognition, publicizing the quality green space and those responsible for it, helps advertising the landscape industry and potential to be adopt as management tool to assist nation green space provisioning. However, issues like the schemes’ ephemeral effect, schemes’ transparency and commodization of green space may hinder the good purpose of recognition and awards if no intervention were made. Findings suggested by transforming the practice of recognition and awards into a certification program and inviting more party during the scheme evaluation process, ones may reduce the issues dwelled within the proposed idea. This research also succeeds to identified 22 imperative factors for quality green space in Malaysia. These 22 factors were subsequently grouped into three key components known as, the physical and environment of green space, the social and experience in green space, and the management and place-keeping of green space. It was suggested that all of these components were highly interlinked and failure from one component may lead to a breakdown for quality green space provisioning. In addition, this study also managed to propose the basic requirement for the practice of recognizing and awards quality green space in Malaysia. Within the proposal, the scheme objective, assessment framework, evaluation criteria, scoring and process were highlighted based on the finding from the literature identified. The interviews also found that there was a demand and positive feedback from the experts on the need for recognition and award practices to bolster the quality green spaces and improve the landscape industry. The information gleaned from this study would be useful to the Malaysian National Landscape Department, green space practitioner, researcher, and local authority working to improve the quality of the place and the quality of life.